Program Pendampingan Pembuatan Modul Ajar Berbasis High Order Thinking Skill di SMP 3 Wonogiri - Novia Wardhani; Elok Fariha Sari; Dhiaz Fajar Widya P; Hafiz Rafi Uddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The merdeka program implemented in some schools has clearly encountered many obstacles. One of them is creating and developing teaching modules. The creation of teaching modules must be consistent with 21st century learning so that teaching modules must be based on higher order thinking skills (HOTS). This is no exception at SMP Negeri 3 Wonogiri. Teachers' understanding of HOTS is reflected in a rubric that includes why and how questions. In fact, to build and strengthen the way of thinking and understanding of HOTS, it must be comprehensive, from learning goals to learning assessment. The purpose of the training proposed by the team to be provided to the teachers of SMP Negeri 3 Wonogiri is to support them so that they can successfully create teaching modules based on HOTS. This service cooperates with SMP 3 Wonogiri and the activation teachers of SMP 4 Pracimantoro. The number participating in the training is 27 teachers from many different subjects. The three-day activity begins with training and ends with a speaker presenting classroom teaching examples.